2022
DOI: 10.3390/machines10010057
|View full text |Cite
|
Sign up to set email alerts
|

Design of a 3D-Printed Hand Exoskeleton Based on Force-Myography Control for Assistance and Rehabilitation

Abstract: Voluntary hand movements are usually impaired after a cerebral stroke, affecting millions of people per year worldwide. Recently, the use of hand exoskeletons for assistance and motor rehabilitation has become increasingly widespread. This study presents a novel hand exoskeleton, designed to be low cost, wearable, easily adaptable and suitable for home use. Most of the components of the exoskeleton are 3D printed, allowing for easy replication, customization and maintenance at a low cost. A strongly underactua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Forcecardiography is a novel technique based on specific wearable force sensors that measure the local forces induced on the chest wall by the mechanical activity of the heart and lungs [ 110 , 111 , 112 , 113 , 114 , 115 ]. FCG signals were first acquired by means of sensors based on force-sensing resistors (FSR), which have already proved suitable for muscle contraction monitoring [ 116 ], gesture recognition [ 117 ], and the control of biosignal-based human–machine interfaces [ 118 ], such as the “Federica Hand” prosthesis [ 119 , 120 , 121 , 122 ] and an upper-limb exoskeleton [ 123 ]. The use of such FSR-based sensors has also been demonstrated for continuous respiratory monitoring [ 114 ].…”
Section: Methodsmentioning
confidence: 99%
“…Forcecardiography is a novel technique based on specific wearable force sensors that measure the local forces induced on the chest wall by the mechanical activity of the heart and lungs [ 110 , 111 , 112 , 113 , 114 , 115 ]. FCG signals were first acquired by means of sensors based on force-sensing resistors (FSR), which have already proved suitable for muscle contraction monitoring [ 116 ], gesture recognition [ 117 ], and the control of biosignal-based human–machine interfaces [ 118 ], such as the “Federica Hand” prosthesis [ 119 , 120 , 121 , 122 ] and an upper-limb exoskeleton [ 123 ]. The use of such FSR-based sensors has also been demonstrated for continuous respiratory monitoring [ 114 ].…”
Section: Methodsmentioning
confidence: 99%
“…Xiao et al [17] employed the ipsilateral setting in their study to help the participants familiarize themselves with the control of a RHO by using FMG sig- nals collected from their ipsilateral forearm. Esposito et al [18] implemented both, contra-and ipsilateral control and selected between those settings depending on the quality of the measurable FMG signal of the user. However, neither of these studies reported any quantitative results of the ipsilateral setting.…”
Section: Feasibility Of Controlling a Rhomentioning
confidence: 99%
“…Thus, for RHO which are primarily targeting assistive applications in activities of daily living, contralateral control is not fully representative. Only a few studies collected FMG signals from the forearm ipsilateral to the RHO [17,18], yet did not evaluate this strategy quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“… Application in medical. ( a ) Use FMG and machine learning techniques to differentiate between grasping and no grasping [ 169 ]; ( b ) textile electrodes integrated with a clothing belt for EIT lung imaging [ 170 ]; ( c ) assisted rehabilitation design of 3D printed hand exoskeleton based on FMG control [ 171 ]; ( d ) EMG biofeedback device for gait rehabilitation [ 172 ]; ( e ) detection of changes in lower extremity muscle impedance properties immediately after functional electrical stimulation-assisted cycling training in chronic stroke survivors [ 173 ]; ( f ) an evaluation of spontaneous respiratory idiopathic pulmonary fibrosis using EIT [ 174 ]. …”
Section: Figurementioning
confidence: 99%